(untitled) (Research, Society and Development, 2022)
Introduction: Inflammatory Bowel Disease (IBD) are diseases characterized by intestinal inflammation, divided into Crohn’s Disease (CD) and Ulcerative Retrocolitis (UC). The cause is still unknown. There are a variety of studies that show the beneficial and potential effect of phytocannabinoids on Inflammatory Bowel Disease. Objective: To evaluate the beneficial effect of Cannabis sativa-derived metabolites in the treatment of IBD, associated with the use of nanotechnology in order to enhance this effect, through a systematic review study. Methodology: This systematic review of the literature of pre-clinical and clinical trials was carried out in the following databases: PUBMED, Science Direct and Scopus from 2012 to 2022. Some combinations of terms were used, such as inflammatory bowel diseases, cannabinoids, cannabidiol and nanotechnology. Results: A total of 418 articles were found in Pubmed, 80 articles in Science Direct and 443 in Scopus. In the end, 6 articles in Pubmed, 10 in Science Direct and 6 in Scopus were considered eligible for analysis according to the established inclusion and exclusion criteria. Discussion: In the analyzed studies, it was noticed that phytocannabinoids represent a promising alternative to treat IBD. Despite the great expectations surrounding these molecules, their physicochemical characteristics represent a significant limitation for their application in the treatment of IBD and other diseases. Therefore, nanotechnology proved to be a way to overcome these problems. Conclusion: In view of all the above, it can be inferred that metabolites derived from Cannabis sativa have great potential for the treatment of inflammatory bowel diseases.